ANALISA BEBAN KALOR SEBAGAI PARAMETER PENENTUAN PEMILIHAN MESIN PENYEGAR UDARA UNTUK DI APLIKASI PADA GEDUNG REKTORAT UNIVERSITAS PASIR PENGARAIAN - Legisnal Hakim (Universitas Pasir Pengaraian, 2014)
Indonesia is a tropical country that has two seasons, dry and rainy seasons, Rokan Hulu is one of the districts in Riau province in the Republic of Indonesia and has a college is the University of sand pengaraian, rector building a two-story office building is on one floor / base comprises ten non psrtisi room, second floor consists of five non- partition space. which is the hottest month for all of Indonesia at the month of May, in the average temperature of 350C outdoors and indoors can reach 300C, in the comfort of working in the room can make people hot and uncomfortable, in the heat load the room is very high, we need to analyze the initial heat load in the room prior to the installation of the engine air refresher. Analysis of heat load is a load that needs dialkukan perimeter latent hea, heat load the interior regio, and the burden of latent heat from the outside air to enter.